AAV2 delivery of the saCas9 gene results in presentation of an HLA-A∗02:01-restricted T cell epitope potent to induce T cell cytotoxicity - Susana S. Najera; Annalisa Nicastri; Sojin Bing; Abdul Mohin Sajib; Nicola Ternette; Ronit Mazor (Molecular Therapy: Methods & Clinical Development, 2025)
In vivo genome editing with CRISPR-Cas9 systems is generating worldwide attention and enthusiasm for the possible treatment of genetic disorders. However, the consequences of potential immunogenicity of the bacterial Cas9 protein and the AAV capsid have been the subject of considerable debate. Here, we model the antigen presentation in cells after in vivo gene editing by in vitro transduction of a human cell line with an AAV2 vector that delivers the Staphylococcus aureus Cas9 transgene. Through HLA class I enrichment, peptide elution, and highly sensitive LC-MS interrogation, we identified a highly conserved saCas9-derived T cell epitope in the catalytic domain of the enzyme that is restricted to HLA-A∗02:01 and induces CD8+ T cell activation and killing. We conclude that AAV delivery of Cas9 results in presentation of a T cell epitope that can activate CD8+ cells and induce killing of the transduced cell, with important ramifications for in vivo genome editing strategies.